Dating banking crises using incidence and size of bank failures: Four crises reconsidered - Chaudron, Raymond; de Haan, Jakob (Journal of Financial Stability, 2014)
We analyze three databases of banking crises and investigate their consistency in the identification and timing of crises. We find that there are large and statistically significant discrepancies between the datasets. We also compare the dating of banking crises according to these databases using information on the number and size of bank failures for four crises for which the timing strongly differs across these databases. We conclude that information on these variables allows determining the timing of banking crises more precisely. Our dating of the four crises corresponds closely with that of Laeven and Valencia.